Explore and describe the factors contributing to workplace stress and burnout among professional nurses working in single-staffed occupational health clinics in Nelson Mandela Bay Metropolitan - Ingram, Unaton Marvin (Stellenbosch : Stellenbosch University, 2025)
Thesis (MNur)--Stellenbosch University, 2025.